Differential Thermoregulatory and Inflammatory Patterns in the Circadian Response to LPS-Induced Septic Shock - Mul Fedele, Malena Lis; Aiello, Ignacio; Caldart, Carlos Sebastián; Golombek, Diego Andrés; Marpegan, Luciano; Paladino, Natalia (Frontiers in Cellular and Infection Microbiology, 2020)
Sepsis is caused by a dysregulated host response to infection, and characterized by uncontrolled inflammation together with immunosuppression, impaired innate immune functions of phagocytes and complement activation. Septic patients develop fever or hypothermia, being the last one characteristic of severe cases. Both lipopolysaccharide (LPS) and Tumor Necrosis Factor (TNF)-α- induced septic shock in mice is dependent on the time of administration. In this study, we aimed to further characterize the circadian response to high doses of LPS. First, we found that mice injected with LPS at ZT11 developed a higher hypothermia than those inoculated at ZT19. This response was accompanied by higher neuronal activation of the preoptic, suprachiasmatic and paraventricular nuclei of the hypothalamus. However, LPS-induced Tnf-α and Tnf-α type 1 receptor (TNFR1) expression in the preoptic area was time-independent. We also analyzed peritoneal and spleen macrophages, and observed an exacerbated response after ZT11 stimulation. The serum of mice inoculated with LPS at ZT11 induced deeper hypothermia in naïve animals than the one coming from ZT19-inoculated mice, related to higher TNF-α serum levels during the day. We also analyzed the response in TNFR1-deficient mice, and found that both the daily difference in the mortality rate, the hypothermic response and neuronal activation were lost. Moreover, mice subjected to circadian desynchronization showed no differences in the mortality rate throughout the day, and developed lower minimum temperatures than mice under light-dark conditions. Also, those injected at ZT11 showed increased levels of TNF-α in serum compared to standard light conditions. These results suggest a circadian dependency of the central thermoregulatory and peripheral inflammatory response to septic-shock, with TNF-α playing a central role in this circadian response.